Evaluation of self-medication among Iraqi pharmacy students - Ahmed, Fadia Thamir; Ali, Ghufran Yousif Mohammed (Journal of Ideas in Health, 2019)
Background: Practicing self-medication is common and a worrisome issue because of irrational drug use. This study aimed to evaluate self-medication knowledge and views among the final year pharmacy students in Iraq. Methods: A cross-sectional descriptive study was conducted from December 2018 to January 2019. A pre-validated and self-administered questionnaire was recruited to survey pharmacy students at the University of Baghdad and Al-Rafedain University College. The Statistical Package for the Social Sciences version 20 (SPSS v. 20) software used to save and analyze the data. Results expressed as numbers and percentages. Results: A total of 344 students (response rate: 94.24%) with a mean age of 22.10 years included in this study. Most of them were female (61.60%). Self-medication was high in the past year (84.88%), and most of them (86.04%) got their medications from pharmacies. About (62.79%) of students used antibiotics as self-medication for a few days, although a significant number were aware of bacterial resistance. The main reasons to self-medicate were quick relief desired, convenience, and avoiding waiting at clinics. The reasons against it were a misdiagnosis, adverse effects' risk, and wrong medication use. Doctor visits sought necessary in cases of worsening symptoms, severe pain, and serious problems. Headache, cough, and diarrhea were the most frequent indications. Conclusion: The self-medication prevalence is high; the knowledge is moderate, and the views about the self-medication concept are generally appropriate.